LATIN AEROBICS: AN EXERCISE WORK-OUT FOR STATIC AND DYNAMIC BALANCE OF CONGENITALLY BLIND CHILDREN - Ignacio, Teresita Dinoc (Universitas Brawijaya, 2020)
The purpose of this study was to investigate the effect of an 8-week Latin aerobics on the static and dynamic balance of children with congenital blindness. Ten (10) congenitally blind children participated in this single-group experimental research. This study tested the static balance of the participants through One Leg Stance (OLS) and the dynamic balance through Timed Up To Go (TUG). The data were analysed through paired t-test. Results of the study showed statistically significant differences during the OLS pre- and post-tests of the right and left legs. No statistically significant differences were observed when the OLS pre- and post-test scores of the right and left legs were compared. The result of the pre- and post-test in the TUG was statistically different. The findings highlighted the effectiveness of Latin aerobics in improving the static and dynamic balance of congenitally blind children.